Next generation sequencing of ancient DNA - Teasdale, Matthew David (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2013)
The application of next generation sequencing (NGS) technologies into the field of ancient DNA has seen a paradime shift in the level of analysis that can be completed using archaeological samples. However, to fully access the power that these techneques provide, certain methological hurdals need to be overcome. This thesis presents case studies that describe the implementation of new techniques to the attainment and analysis of aDNA to address these problems, as well as the use of a new substrate (parchment) for the NGS analysis of aDNA.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.